1997
DOI: 10.1108/13552519710176863
|View full text |Cite
|
Sign up to set email alerts
|

The status of maintenance management in Swedish manufacturing firms

Abstract: Presents a model of five linked maintenance management components (strategy, human aspects, support mechanisms, tools/techniques and organization). Analyses the present status of these components in Swedish manufacturing firms through a survey of 284 respondents. Shows that fewer than half have written maintenance strategies or computerized maintenance information systems and several give maintenance low status. The figures are lowest in small firms and in the timber industry. Preventive maintenance at fixed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 16 publications
2
60
0
8
Order By: Relevance
“…The status and role of maintenance are not highly recognised in companies. For example, more than onehalf of the respondents of the survey indicated that they do not have any written maintenance strategy (this is similar to a result published by a previous study, see Jonsson, 1997). Moreover, the maintenance department still belongs from an organisational point of view to the production department.…”
Section: Conclusion and Commentssupporting
confidence: 75%
See 2 more Smart Citations
“…The status and role of maintenance are not highly recognised in companies. For example, more than onehalf of the respondents of the survey indicated that they do not have any written maintenance strategy (this is similar to a result published by a previous study, see Jonsson, 1997). Moreover, the maintenance department still belongs from an organisational point of view to the production department.…”
Section: Conclusion and Commentssupporting
confidence: 75%
“…Thus, the contribution of maintenance departments in designing and improving production processes, and helping the purchasing department in selecting the right manufacturing equipment is considered an essential element of maintenance practice. Jonsson (1997) emphasised that feedback control loop of maintenance data is necessary to reduce the life cycle costs at an early stage, and implementation of a Deming plan-do-check-act-cycle (PDCA) is important to allow continuous improvement.…”
Section: Innovation and Growth Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Research by Robson (2010) found that maintenance organizations in the North East of England were not creating maintenance strategies and linking them to manufacturing and business goals. However, this may not be an issue unique to the UK because similar concerns were raised in Sweden by the research of Jonsson (1997).…”
Section: Introductionmentioning
confidence: 99%
“…This should be defined with specific, measurable, achievable, realistic and timely objectives (SMART) (Cross and Lynch, 1989). These objectives should be coherently aligned to the manufacturing and business goals (Jonsson, 1997). Once the "future state" objectives are established, the "current state" is measured in relation to these objectives.…”
Section: Processmentioning
confidence: 99%